PENGUKURAN KINERJA MENGGUNAKAN METODE BALANCED SCORECARD DI PERGURUAN TINGGI SWASTA XYZ PADANG - Arifa Sabardilla; Rahmi Fahmy (STIE AMKOP, 2020)
Competition between universities in this day and age is getting tougher. Higher education is requested to be able to develop an academic community that is competitive, creative, innovative, skilled, and able to develop and apply knowledge in accordance with the values of the Humanities. Colleges are competing to improve their quality so that customer confidence increases. Therefore we need a performance measurement system that can be used by management to evaluate its performance. The results of this evaluation will be very important to plan and determine strategic steps and strategies to achieve the institution's vision, mission and goals. One method that can be used as a performance measurement tool is the balanced scorecard method. The balanced scorecard is an organizational performance measurement model that not only emphasizes how far the success of the organization is seen from a financial perspective, but also from the perspective of customers, internal business processes, and learning and growth. Therefore, the purpose of this study is to determine the performance of the XYZ Padang College when measured using the Balanced Scorecard method. The final result of this study is a strategy map that can help XYZ Padang College in carrying out its institution. Keywords: performance measurement, balanced scorecard, college, strategy map